Analisis dan Rancangan User Experience Website OAIL Menggunakan Metode Task Centered System Design (TCSD) - Yulita, Winda; Algifari, Muhammad Habib; Rinaldi, Daniel; Praseptiawan, Mugi (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The increase in internet service users in obtaining information and knowledge has made many institutions or organizations begin to create and design websites. One of the institutions that started to build a website is UPT OAIL. In the process of forming the OAIL website, a good User experience (UX) design is needed because it affects user satisfaction in using the website. The analysis and design of user experience in this study uses the Task Centered System Design (TCSD) method. The TCSD method can identify user needs and task needs. The stages in the research are user identification and observation, user and organization requirements analysis, design as scenario and walkthrough evaluate. In this study, identification and observation were carried out by interviewing UPT OAIL staff as well as prospective users. The test is based on the usability method using USE Questionare on the ease of use dimension. The results of the study obtained that the interpretation score for testing the ease of use dimension was 94.2% with the conclusion that the average user or respondent chose the design of each page and the features made were very easy to use.